2019
DOI: 10.18280/i2m.180205
|View full text |Cite
|
Sign up to set email alerts
|

U-shape Acoustic Liquid Densitometer

Abstract: The growing interest in measuring density of liquids has led to the need to develop new types of densitometers that can be used in several applications. The purpose of this work is to propose a simple densitometer based on measuring the frequency of created standing wave with a tube filled by a liquid under test. The developed approach is utilized to obtain a relationship between the density of some liquids and the frequency. The data acquisition and signal processing are carried out by LabVIEW software. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For reliability of results, all combinations were repeated three times and tested at a constant temperature of 22 • C in a similar manner to research undertaken by Rechberger [23] which was monitored by a climatic chamber, as shown in the system schematic in Figure 4 and equipment setup in Figure 5. LabVIEW software was used on a laptop to measure and control the system, as implemented in similar studies [19,[44][45][46][47]. A National Instruments USB X Series Data Acquisition Device [48] was used as the interface between the physical model and the laptop.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…For reliability of results, all combinations were repeated three times and tested at a constant temperature of 22 • C in a similar manner to research undertaken by Rechberger [23] which was monitored by a climatic chamber, as shown in the system schematic in Figure 4 and equipment setup in Figure 5. LabVIEW software was used on a laptop to measure and control the system, as implemented in similar studies [19,[44][45][46][47]. A National Instruments USB X Series Data Acquisition Device [48] was used as the interface between the physical model and the laptop.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Their work also showed how to take into account appropriate amendments [9,10]. The main disadvantages of the method are the complexity of apparatus and the effect of the pressure inside the tube [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other works [14][15][16][17] illustrate several techniques, based on acoustic measurement that are applicable to measure several physical and chemical parameters such as: density of gases, temperature, displacement and concentration. These methods are based on creating a standing wave within a resonance tube (forced or free resonance mode of operation) and then the physical phenomenon based on acoustic measurement is acquired by a microphone and signal processing is performed using LabVIEW software [16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation